A Comprehensive Study on the Activity and Deactivation of Immobilized Lecitase Ultra in Esterifications of Food Waste Streams to Monoacylglycerols. Issue 5 (19th March 2013) - Gonçalves, Karen M.; Sutili, Felipe K.; Júnior, Ivaldo I.; Flores, Marcella C.; Soter de Mariz e Miranda, Leandro; Leal, Ivana C. R.; Cordeiro, Yraima; Luque, Rafael; de Souza, Rodrigo Octavio M. Alves
Abstract Lecitase Ultra was immobilized on Amberlites XAD2 and XAD4, through physical entrapping under conventional stirring or ultrasound irradiation, and characterized by standard techniques. The resulting immobilized biocatalysts were utilized in the valorization of an acidic food‐derived residue from a palm oil refining process to produce monoacylglycerols from isopropylidene glycerol under batch and continuous flow conditions. Results indicated that the immobilized biocatalysts could moderately convert the food waste residue (max. conversion 50–60 %), exhibiting interesting stability under continuous flow conditions.